Elections without order : Russia's challenge to Vladimir Putin - Rose, Richard, 1933- (Cambridge University Press, 2002)
Russians want both free elections and order. Russia's political elites have had no difficulty in supplying a great choice of candidates and parties, but order has been in short supply. This is the challenge that Russia presents to Vladimir Putin. The authors present unrivalled survey and polling data.